Study on acute encephalitis syndrome in children and their correlation with clinical parameters and etiological factors - Reddy, Maram Nagarjuna; Belavadi, Gangadhar; Priyanka, Vaka Hari (International Journal of Contemporary Pediatrics, 2019)
Background: Acute encephalitis is the clinical diagnosis of children with acute onset of symptoms and signs of inflammatory lesions in the brain. It must be diagnosed promptly for saving life and preserving brain functions. Authors objectives was to determine the profile and outcome of children admitted with Acute Encephalitis Syndrome (AES) and to identify etiological factors. Methods: Study consist of a retrospective analysis of hospital records of children up to 15 years of age admitted with a diagnosis of AES in the pediatric ward, Narayana medical college, Nellore from January 2018 to June 2019. Results: In a total of 30 patients of AES, clinical features like fever (100%), altered sensorium (100%), convulsion (40%), headache (45%) and neuro deficit (40%) and vomiting (50%). The average Glasgow coma scale at admission was 8. There are 55% of cases in the 5 to15 yr age group (p>0.05). Both Encephalitis (56.6%) and meningitis (43.3%) were documented significantly more in males as compared to females (p<0.01). Twenty-one cases are discharged, eight expired, and 1 case was referred (p<0.001). JE IgM positive cases contributed to 36.6%, of which eight males and three females recorded between 5-15 years. Male children are more likely to play outdoors where the mosquito vector of the disease is abundant. Conclusions: JE has significant morbidity and mortality, can be prevented by immunization, and reduced if supportive interventions are provided in time. Preventive measures must be taken for 5-15 years of age group those playing outdoors, going to school or agriculture fields predisposing them to vector mosquito bite.